Mandibular Thickness Measurements as Predictive Tool for Specific Dental Disorders in Alpacas (Vicugna Pacos) - Proost, Kirsten; Pardon, Bart; Vlaminck, Lieven (Frontiers in Veterinary Science, 2022)
Background Oral health in alpacas is often neglected until severe dental disease becomes evident under the form of a pronounced mandibular swelling with or without fistulation. Mandibular thickness measurements might serve as an easy tool to screen for early increases in thickness thereby identifying alpacas which could benefit from an oral examination. Objective To study specific risk factors, including age, gender, level of performed measurements and dental disorders, associated with mandibular thickness in alpacas. To determine suitable cutoff values for mandibular thickness at specific locations for the development of a diagnostic test to identify animals with dental disorders. Study design Cross-sectional study Methods Mandibular thickness was measured at standardized locations in 216 alpacas using a Vernier-caliper. Risk factors for an increased mandibular thickness were collected through oral examination in sedated animals and by interview of the respective owner. A multivariable linear mixed model was built to identify factors associated with mandibular thickness. Cutoff values for specific dental disorders were obtained after receiver operating characteristics (ROC)-curve analysis. Results Mandibular thickness was 0.43 ± Standard Error 0.21 mm (95% Confidence interval (CI)= 0.02-0.84 mm) higher at locations where interproximal gum recession was present (P= .039). Severe dental disease caused an increase in thickness of 1.90 mm (95% CI= 1.29-2.51 mm) (P<.001). Mandibular thickness with a cutoff of 19.4 mm showed a high accuracy for predicting severe dental disease (Se= 0.41; Sp= 0.92). Specifically, thickness at a level perpendicular to the medial canthus of the eye proved a more precise predictor for severe dental disease (AUC, 0.85; 95% CI 0.74-0.96; P<.001) with a lower cutoff of 18.5 mm and Sn and Sp of 0.52 and 0.82, respectively. Main limitations No radiographic or computed tomographic studies were available to support the diagnosis of dental and/or apical disease. Conclusion Mandibular thickness measurements in alpacas can aid early detection of animals in need of specialized dental care. Most animals with an increased mandibular thickness suffer from advanced dental disease. However, routine dental examinations remain necessary to allow the early detection of dental disorders in alpacas.